Mediating Effects of Factors Influencing Career Satisfaction of Women Academicians in Higher Education - Kurup, Ajit J.; Pandey, Shikha; Charfare, Mushira (Prabandhan: Indian Journal of Management, 2020)
India is expected to be the largest higher - education system in the world by 2030, overtaking China and USA. With over 900 institutions as in 2017–18 and the largest youth population, it has been predicted that one in every fourth individual graduating will belong to Indian educational institutions. A deeper analysis of the All India Survey of Higher Education (AISHE, 2017–18) revealed a decline of teachers in higher education, thus making it imperative to understand the reasons for the decline, especially among women academicians. Women academicians account for 42% of total higher education teachers’ population with less than 25% at professor level and only a handful occupy the coveted post of vice-chancellor. While various individual and organizational factors may be at play, this study used structural equation modeling to comprehend the influence of career advancement in the career satisfaction of women academicians. Data were collected from 351 women academicians working in higher education institutions in Indian cities using a structured questionnaire, which showed Career Advancement as a full mediator of Career Satisfaction which in turn was influenced by Career Management Techniques and Work – Life Balance factors. Confirmatory factor analysis was used to determine convergent and discriminant validities. The fitment of the model was ascertained by evaluating structural model and the hypothesized relationships. The findings highlighted the importance of Career Advancement and its influence on Career Satisfaction. This research reiterated the need for policy makers, government, and higher education institutions to focus on ensuring a clear career path with suitable opportunities to ensure the longevity and success of women academicians.